Postoperative Outcomes in Vedolizumab-Treated Patients Undergoing Major Abdominal Operations for Inflammatory Bowel Disease: Retrospective Multicenter Cohort Study. Issue 4 (2nd March 2018) - Lightner, Amy L; Mathis, Kellie L; Tse, Chung Sang; Pemberton, John H; Shen, Bo; Kochhar, Gursimran; Singh, Amandeep; Dulai, Parambir S; Eisenstein, Samuel; Sandborn, William J; Parry, Lisa; Stringfield, Sarah; et al.
Abstract: Background: Vedolizumab is now widely available for the treatment of moderate to severe ulcerative colitis (UC) and Crohn's disease (CD). We sought to quantify the rates of postoperative complications with preoperative vedolizumab compared with anti–tumor necrosis factor (anti-TNF) therapy. Methods: A multicenter retrospective review of adult inflammatory bowel disease (IBD) patients who underwent an abdominal operation between May 20, 2014, and December 31, 2015, was performed. The study cohort was comprised of patients who had received vedolizumab within 12 weeks of their abdominal operation, and the control cohort was IBD patients who had received anti-TNF therapy. Results: A total of 146 patients received vedolizumab within 12 weeks before an abdominal operation (64% female; n = 93; median age, 33 years; range, 15–74 years), and 289 patients received anti-TNF therapy (49% female; n = 142; median age, 36 years; range, 17–73 years). Vedolizumab-treated patients were younger ( P = 0.015) and were more likely to have taken corticosteroids ( P < 0.01) within the 12 weeks before surgery. Vedolizumab-treated patients had a significantly increased risk of any postoperative surgical site infection (SSI; P < 0.01), superficial SSI ( P < 0.01), deep space SSI ( P = 0.39), and mucocutaneous separation of the diverting stoma ( P < 0.00) as compared with patients taking anti-TNF therapy. On multivariate analysis, after adjusting for body mass index, steroids at the time of operation, and institution, exposure to vedolizumab remained a significant predictor of postoperative SSI ( P < 0.01). Conclusions: We observed that vedolizumab-treated patients were at significantly increased risk of postoperative SSIs after a major abdominal operation, as compared with anti-TNF-treated patients.